2017
DOI: 10.1002/jso.24616
|View full text |Cite
|
Sign up to set email alerts
|

Clinical accuracy of preoperative breast MRI for breast cancer

Abstract: Breast MRI provides greater accuracy for a third of patients undergoing preoperative MGM and U/S. Mammographic calcifications were associated with MRI clinical accuracy for patients with invasive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) has been shown to be the most accurate diagnostic tool for breast cancer diagnosis and follow-up care [6] and provides greater accuracy for tumor size prediction than mammography and ultrasound in patients not receiving neoadjuvant therapy [7]. Several studies have investigated the diagnostic power of breast MRI during and/or after NACT [813].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been shown to be the most accurate diagnostic tool for breast cancer diagnosis and follow-up care [6] and provides greater accuracy for tumor size prediction than mammography and ultrasound in patients not receiving neoadjuvant therapy [7]. Several studies have investigated the diagnostic power of breast MRI during and/or after NACT [813].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the early detection and accurate preoperative staging and treatment of breast cancer are crucial to improve the prognosis (11,12). Many studies have been reported on the value of US combined with MRI detection in breast cancer staging, but most of them only focus on T staging and diagnosis efficiency, few only on N and M staging (13). Therefore, in this study, the diagnostic value of US combined with MRI in the T, N and M staging of breast cancer was analyzed, in order to provide a more effective, sensitive and accurate detection program for the early diagnosis and accurate staging, improving the efficacy of patients' subsequent treatment and the prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the management on radiologic tumor size and thus clinical stage in these cases can result either in a procedure that would otherwise not be necessary or on the other hand conservative and thus inadequate treatment. A recent study by Tseng et al 10 assessed the accuracy of MRI alone versus a combination of USG plus MG in accurate estimation of tumor size. Interestingly, instead of using an absolute value of 2 mm or 5 mm, they used a size difference of less than 33% as concordant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Some authors looked into tumor size concordance with respect to different imaging modalities, but many of these studies were limited, either by small sample size; because only a specific type of tumor was considered based on the exclusion criteria; or because only highly specialized techniques such as magnetic resonance imaging (MRI) was used, which is not as widely available or used as ultrasonography (USG) in the assessment of the breast carcinomas. [10][11][12][13][14][15][16][17][18][19][20][21] Moreover, most studies considered a size difference of AE5 mm to be concordant, 11,13 which is significant enough to result in a change of stage classification in a considerable number of cases. We compared pathologic tumor size with ultra-sonographic (USG) size.…”
Section: Introductionmentioning
confidence: 99%